2021
DOI: 10.52586/5051
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in the gut microbiota and fecal metabolites in an adolescent valproic acid-induced rat autism model

Abstract: Introduction 3. Materials and methods 3.1 Animals 3.2 Construction of the VPA-induced rat model of autism 3.3 Experimental groups 3.4 Collection of feces 3.5 16S rRNA gene sequencing 3.6 UHPLC-MS based untargeted metabolomics 3.7 Statistical analysis 4. Results 4.1 Taxonomical characterization of the gut microbiota in male and female VPA rats 4.2 Characteristics of fecal metabolites in male and female VPA rats 4.3 Differential metabolites and KEGG pathways in male and female VPA rats 4.4 Correlation between ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…In this way, the effect of SMPS on the VPA-induced intestinal flora of model rats can be more accurately explored. Through 16S rRNA gene sequencing analysis, we found that the richness and diversity of the GM showed significant differences among the SMPS, VPA and control rats, which is consistent with the findings of a previous study (Gu et al, 2021). A recent report found that the richness and diversity of gut microbiota did not differ between VPA and control groups, while the overall composition of gut microbiota was significantly different (Gu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…In this way, the effect of SMPS on the VPA-induced intestinal flora of model rats can be more accurately explored. Through 16S rRNA gene sequencing analysis, we found that the richness and diversity of the GM showed significant differences among the SMPS, VPA and control rats, which is consistent with the findings of a previous study (Gu et al, 2021). A recent report found that the richness and diversity of gut microbiota did not differ between VPA and control groups, while the overall composition of gut microbiota was significantly different (Gu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…A strong correlation between gut microbiota and fatty acids has been reported in autistic rats [98]. In terms of specific fatty acid, mice injected with valproic acid showed higher abundance of Candidatus_Saccharimonas which suggests a direct link between gut microbiota and fecal metabolites [99]. In line with our results, a positive regulation between Parabacteroides and SCFAs has been demonstrated in human fecal microbiota identified by in vitro fermentation [100].…”
Section: Discussionsupporting
confidence: 89%
“…To investigate sexual dimorphism of VPA effects, several studies have compared gender-specific alterations in maternally VPA-treated offspring [19][20][21][22][23]. Evidence shows gender-specific changes in the immune responses [19,20,22,24], cell density of cerebellum [23,25], network connectivity [26], anandamide signaling [27], attentional processing [28], and composition of gut microbiota [29] in maternally VPA-treated animal offspring. These sexual dimorphisms may be related to histone deacetylase (HDAC) inhibition by VPA, as Konopko et al have reported differential epigenetic modification of Bdnf genes in maternally VPA-treated fetal brains of different genders [24].…”
Section: Vpa-induced Asd-like Animal Modelsmentioning
confidence: 99%